Sosialisasi dan Pelatihan Pembuatan Hand Sanitizer Alami di SMK Nurul Ilmi sebagai Upaya Edukasi Kesehatan Berbasis Lingkungan: Pengabdian - Endang Verawati; Sunanto; Syerina Raihatul Jannah; Waliah Nur Rahayu; Tika Handayani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This Community Service (PkM) activity was held at SMK Nurul Ilmi, Jalan Palembang–Betung Km.18, Banyuasin Regency. This school offers two expertise programs, namely Computer Network Engineering and Islamic Banking. Although not a health-based school, students and teachers need to receive education on clean and healthy living behaviors (PHBS), especially maintaining hand hygiene as a disease prevention measure. The limited availability of soap and clean water in schools makes hand sanitizer a practical solution. However, commercial products generally contain harsh chemicals and are quite expensive. This condition encourages the need for alternative natural products that are safe, economical, and environmentally friendly. Betel leaves (Piper betle L.) contain flavonoids and tannins that have natural antibacterial and antiseptic properties, while limes (Citrus aurantifolia Swingle) contain vitamin C, flavonoids, and essential oils that function as antimicrobials. The combination of these two ingredients can be used to make a natural hand sanitizer. This activity aims to increase the knowledge, awareness, and skills of students and teachers in making natural hand sanitizers based on local ingredients. The implementation method included outreach, training, and hands-on practice. Participants were taught how to process betel leaves and limes to produce a hygienic, effective, and fresh-smelling product. The activity results showed a more than 50% increase in participants' understanding of the benefits of natural ingredients and how to make them. Participants were also motivated to develop this product as a form of independence and a simple business opportunity within the school environment.